Non-neutral clonal selection and its potential role in mammalian germline stem cell dysfunction with advancing age - Stolzenbach, Victor; Woods, Dori C.; Tilly, Jonathan L. (Frontiers in Cell and Developmental Biology, 2022)
The concept of natural selection, or ‘survival of the fittest’, refers to an evolutionary process in nature whereby traits emerge in individuals of a population through random gene alterations that enable those individuals to better adapt to changing environmental conditions. This genetic variance allows certain members of the population to gain an advantage over others in the same population to survive and reproduce in greater numbers under new environmental pressures, with the perpetuation of those advantageous traits in future progeny. Here we present that the behavior of adult stem cells in a tissue over time can, in many respects, be viewed in the same manner as evolution, with each stem cell clone being representative of an individual within a population. As stem cells divide or are subjected to cumulative oxidative damage over the lifespan of the organism, random genetic alterations are introduced into each clone that create variance in the population. These changes may occur in parallel to, or in response to, aging-associated changes in microenvironmental cues perceived by the stem cell population. While many of these alterations will be neutral or silent in terms of affecting cell function, a small fraction of these changes will enable certain clones to respond differently to shifts in microenvironmental conditions that arise with advancing age. In some cases, the same advantageous genetic changes that support survival and expansion of certain clones over others in the population (viz. non-neutral competition) could be detrimental to the downstream function of the differentiated stem cell descendants. In the context of the germline, such a situation would be devastating to successful propagation of the species across generations. However, even within a single generation, the ‘evolution’ of stem cell lineages in the body over time can manifest into aging-related organ dysfunction and failure, as well as lead to chronic inflammation, hyperplasia, and cancer. Increased research efforts to evaluate stem cells within a population as individual entities will improve our understanding of how organisms age and how certain diseases develop, which in turn may open new opportunities for clinical detection and management of diverse pathologies.